Modernizing Digital Forensics Education: Integrating Specialized Cyber-Expertise into Legal and Investigative Curricula - Amiriddin, Anorboyev (CV. Bimbingan Belajar Assyfa, 2026)
The rapid digitalization of sectors and the rise of transnational cybercrimes have created an urgent need to reform forensic practices in the Republic of Uzbekistan. Current reliance on general forensic computer-technical expertise is becoming insufficient due to the technical complexity of modern telecommunications and digital environments. This study evaluates the limitations of existing frameworks and proposes a comprehensive classification of specialized expertise, including telecommunications network, infrastructure, software, and cryptographic examinations, to ensure the admissibility and integrity of digital evidence. By utilizing a comparative analysis of international practices in developed nations and examining the current technical gaps in investigative procedures, this research identifies critical shortcomings in personnel training and the utilization of specialized forensic tools. The findings demonstrate that a multifaceted approach to expert examination is essential for keeping pace with evolving cyber threats. Furthermore, this research does not only propose a legislative update for cyber-expertise but also provides a systematic educational foundation to improve the professional competency of investigators and judicial experts in handling complex cybercrimes. Implementing these reforms will bridge the gap between technical advancements and legal proceedings, ultimately enhancing the efficacy of cybercrime investigation and ensuring robust cybersecurity compliance.